The quest for quality services: does SERVQUAL perfectly measure the university services? - Himphinit, Musakkid; Mohd Ali, Hairuddin (IIUM Press, 2011)
A brief study on service quality using Parasuraman's SERVQUAL framework namely tangibles, reliability, assurance, empathy and responsiveness. Future study is also discussed and suggested.